Changes in peripheral blood T-cell balance after percutaneous tumor ablation. Issue 6 (2nd November 2017) - Takaki, Haruyuki; Imai, Naoko; Thomas, Contessa T.; Yamakado, Koichiro; Yarmohammadi, Hooman; Ziv, Etay; Srimathveeravalli, Govindarajan; Sofocleous, Constantinos T.; Solomon, Stephen B.; Erinjeri, Joseph P.
Abstract: Purpose: To evaluate the changes in T-cell balance in peripheral blood following percutaneous tumor ablation. Material and methods: Patients underwent thermal ablation including radiofrequency ( n  = 9) and microwave ablation ( n  = 5), or cryoablation ( n  = 5). Target tumors were located in the lung ( n  = 7), soft tissue ( n  = 5), liver ( n  = 4), and bone ( n  = 3). Patient peripheral blood samples were collected before and within 14 days after ablation. Peripheral blood populations of cytotoxic T-cells (CTL), type-1 (Th 1) and type-2 helper T-cells (Th 2), and regulatory T-cells (Treg ) were measured using flow cytometry. Changes in CTL/Treg and Th 1/Th 2 ratios before and after ablation therapy were compared using paired t- tests. Results: Peripheral blood CTL population (27.5 ± 2.1% to 30.2 ± 2.5%, p  < .03) and CTL/Treg ratios (18.8 ± 3.7% to 21.6 ± 3.6%, p  < .05) increased significantly after ablation. Although a significant increase in CTL/Treg ratios was found after heat-based ablation (18.0 ± 4.4% to 21.6 ± 4.7%, p  < .02), it remained unchanged after cryoablation (21.0 ± 7.0% to 21.5 ± 4.3%, p  = .92). Th 1/Th 2 ratio (13.7 ± 3.0% to 17.2 ± 3.5%, p  = .12) remained unchanged after ablation. Conclusion: Ablation therapy alters the T-cell balance by increasing the systemic CTL/Treg, ratio. Heat-based ablation might be a more effective approach than cryoablation to enhance systemic anti-tumor immunity.